A Hybrid NSGA-II - AHP Approach for Multi-Objective Optimization of Two-Stage Helical Gearboxes: Cross-Sectional Area-Efficiency Trade-Off - Giang, Tran Ngoc (European Journal of Applied Sciences, 2026)
In modern mechanical systems, the design of two-stage helical gearboxes requires a balance between compactness and performance. This study proposes a hybrid multi-objective optimization approach integrating NSGA-II and AHP to minimize cross-sectional area and maximize efficiency. A mathematical model is developed to represent design variables, objectives, and constraints. NSGA-II generates a Pareto-optimal solution set, revealing the trade-off between compactness and efficiency, while AHP is used to select the most suitable design based on objective priorities. The results demonstrate that the proposed approach provides effective optimization and supports rational decision-making in gearbox design. This work offers a practical methodology for developing compact and high-performance transmission systems.